The Relationships among Satisfaction with Social Support, Quality of Life, and Survival 5 to 10 Years after Heart Transplantation - White-Williams, Connie (2013)
BACKGROUND: Despite the fact that social support has been found to be important to cardiovascular health, there is a paucity of information regarding the relationship between social support and outcomes long-term after heart transplantation (HT). OBJECTIVES: Thus, the purposes of our retrospective analyses of a prospective, longitudinal study were to examine (1) the relationship between satisfaction with social support and post HT health-related quality of life (HRQOL) and survival, and (2) whether two types of social support (emotional and tangible) were predictors of survival and HRQOL. METHODS: Data were collected from 555 HT patients over a 5-year period (78% male, 88% white, mean age=53.8 years at time of transplant) at 4 U.S. medical centers using the following instruments: Social Support Index, QOL Index, HT Stressor Scale, Jalowiec Coping Scale, and medical records review. Statistical analyses included t-tests, correlations, Kaplan-Meier survival actuarials, and linear and multivariable regression. RESULTS: Patients were very satisfied with overall social support from 5 to 10 years after HT (0=very satisfied, 1=very dissatisfied) which was stable across time (p = 0.74). Satisfaction with emotional social support (p = 0.53) and tangible social support (p = 0.61) also remained stable over time. When stratified into low, medium and high levels of satisfaction, satisfaction with social support was not related to survival (p = 0.24). At 5 years, overall satisfaction with social support was a predictor of HRQOL ( r(2)=.59, p<.0001), and satisfaction with emotional social support was a predictor of HRQOL at 10 years post HT ( r(2)=.66, p<.0001). CONCLUSIONS: Patients were very satisfied over time with emotional and tangible social support. While social support explained QOL outcomes, it did not predict survival. Knowledge of relationships among social support, stress, and outcomes may assist clinicians to address social support needs and resources long-term after HT.